THE REPRESENTATION OF THE MYTHOLOGICAL TANUKI IN STUDIO GHIBLI’S POM POKO: BARTHESIAN SEMIOTIC ANALYSIS - Wedhowerti, Wedhowerti (Universitas Islam Sumatera Utara (UISU), 2024)
Studio Ghibli’s animated film Pom Poko presents the tanuki or raccoon dogs which, according to the Japanese myth, have magical power of impersonating human or shape-lifting. Mythology refers to the study of religious or heroic legends and tales created by particular communities or societies. Having the setting in the 1960s of post-war Japan, this animated film mediates the meaning of the tanuki’s moves in selected scenes. Therefore, Barthesian semiotic model is employed as semiotics itself is concerned with the film and its representation. This research is then aimed at finding out the representation of the tanuki. Employing qualitative method, this research selects six data in the forms of images to analyze. The results yield that the tanuki are the heroes of environmental conservation by struggling and using force for the sake of their environment, jungle, food sources, living territory, and future cubs. Their moves of defending nature represent their ecological terroristic ideology or ecoterrorism.